Morfološke značilnosti košarkaric, starih 14 in 15 let, ki nastopajo v skupinah A in B evropskega prvenstva - Erčulj, Frane (Šport (Ljubljana), 2010)
The study basically aimed to establish and analyse the morphological characteristics of elite female basketball players aged 14 and 15 playing in Divisions A and B of the European Championship as well as to compare these two groups of players. For this purpose, a sample was used consisting of 51 female basketball players aged 14.67 ( 0.47) of whom 22 played in Division A and 29 in Division B of the European Championship. The results show that the Division A players were taller on average in all three playing positions. The forwards of Division B had a higher percentage of fat mass on average, a more pronounced mesomorphic component and a less pronounced ectomorphic component of the somatotype compared to the Division A forwards. The Division A centres had a considerably higher percentage of fat mass on average as well as higher values of endomorphic and lower values of ectomorphic components than the Division B centres.
Keywords: dekleta; igralna mesta; košarka; meritve; morfološke lastnosti; raziskave